2018
DOI: 10.1016/j.saa.2018.03.064
|View full text |Cite
|
Sign up to set email alerts
|

A combined photophysical and computational study on the binding of mycophenolate mofetil and its major metabolite to transport proteins

Abstract: Binding of the immunosuppressive agent mycophenolate mofetil (MMP) and its pharmacologically active metabolite mycophenolic acid (MPA) to human serum albumin (HSA) and α-acid glycoprotein (HAAG) has been investigated by means of an integrated approach involving selective excitation of the drug fluorophore, following their UV-A triggered fluorescence and docking studies. The formation of the protein/ligand complexes was evidenced by a dramatic enhancement of the fluorescence intensity and a hypsochromic shift o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Molecular modeling experiments conducted by Ma et al suggested that a hydrogen bond is formed between oxygen atoms of the carboxyl group of MP and the nitrogen atom of Arg257 in subdomain IIA . Vendrell-Criado et al also used a molecular modeling approach and reported the formation of a hydrogen bond between the phenol group of MP and the side chain of Arg257, and they also reported electrostatic interactions between the carboxylate moiety of MP and the guanidinium groups of Arg222 and Arg212, which are located close to Trp214 . Despite this discrepancy, our crystallographic data indicated that the isobenzofuran group of MP is located at the entrance of the subdomain IIA pocket and forms a hydrogen bond with Arg257 through its carboxyl group.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Molecular modeling experiments conducted by Ma et al suggested that a hydrogen bond is formed between oxygen atoms of the carboxyl group of MP and the nitrogen atom of Arg257 in subdomain IIA . Vendrell-Criado et al also used a molecular modeling approach and reported the formation of a hydrogen bond between the phenol group of MP and the side chain of Arg257, and they also reported electrostatic interactions between the carboxylate moiety of MP and the guanidinium groups of Arg222 and Arg212, which are located close to Trp214 . Despite this discrepancy, our crystallographic data indicated that the isobenzofuran group of MP is located at the entrance of the subdomain IIA pocket and forms a hydrogen bond with Arg257 through its carboxyl group.…”
Section: Discussionmentioning
confidence: 52%
“…A modeling study of the HSA−MP-Mof complex reported previously by Vendrell-Criado indicated that the binding position of MP-Mof is located in the inner pocket of subdomain IIA, in contrast to that of MP, as determined by crystal structure analysis. 14 This model structure showed that the isobenzofuran group of MP-Mof forms hydrogen bonds with Arg218 and Arg222. The binding position of the morpholine ring of MP-Mof is near Gln196 and the disulfide bonds of Cys200/Cys246 or Cys245/Cys253, whereas this pocket appears to be closed by Tyr150 in the HSA−MP complex structure.…”
Section: ■ Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The equipments employed for recording the emission spectra, for determining the fluorescence lifetimes and for transient absorption spectroscopic measurements have been described elsewhere [28,29]. Experiments were performed at 22 °C; concentration of CMZ was 2 × 10 -5 M and concentration of SVN was 6.3 × 10 -3 M.…”
Section: Fluorescence and Laser Flash Photolysis Experimentsmentioning
confidence: 99%